2019
DOI: 10.1002/ese3.522
|View full text |Cite
|
Sign up to set email alerts
|

An ANN‐based failure pressure prediction method for buried high‐strength pipes with stray current corrosion defect

Abstract: With continued increasing construction of both electrified facilities and buried high‐strength pipelines in China, stray current corrosion defects have become an nonignorable threat for these pipelines. A comprehensive investigation on a new failure pressure prediction model for high‐strength pipes with stray current corrosion defects was conducted in this study. The mechanism of stray current corrosion in steel pipes was firstly elaborated in brief. After that, a parameterized finite element model for stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Artificial neural network (ANN) technology is used in the simulation, abstraction, and simplification of brain function, and it has the functions of learning, association, memory, and a highly nonlinear prediction ability. It has been widely used in burst pressure prediction of oil and gas pipelines 23 . In this study, ANN technology is used to predict the burst pressure of corroded steel pipelines.…”
Section: An Artificial Neural Network Based Burst Pressure Prediction Methods For Corroded Steel Pipelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial neural network (ANN) technology is used in the simulation, abstraction, and simplification of brain function, and it has the functions of learning, association, memory, and a highly nonlinear prediction ability. It has been widely used in burst pressure prediction of oil and gas pipelines 23 . In this study, ANN technology is used to predict the burst pressure of corroded steel pipelines.…”
Section: An Artificial Neural Network Based Burst Pressure Prediction Methods For Corroded Steel Pipelinesmentioning
confidence: 99%
“…It has been widely used in burst pressure prediction of oil and gas pipelines. 23 In this study, ANN technology is used to predict the burst pressure of corroded steel pipelines. The burst pressure of the pipeline can be predicted based on the corrosion defect parameters and the axial force, by adopting the ANN technology.…”
Section: Effect Of Corrosion Width On the Burst Pressure Of A Corroded Pipelinementioning
confidence: 99%
See 1 more Smart Citation
“…The effective depth of the metal loss combined from C3D3 and C3D4 calculated according to Equation (4) is equal to dnm = 4.0 mm. The results of the plastic burst pressure calculations according to Equations (5) and (6), in the three analysed cases of colonies of the volumetric defects, are summarized in Table 4. Table 4, it can be concluded that rupture pressure calculated according to Det Norske Veritas Recommended practice for every analysed group of flaws is in the difference range of 2 bar compared to the assessment of the individual features.…”
Section: In-line Inspection Indications Clusteringmentioning
confidence: 99%
“…However, a lot of studies deal with investigation of strength and structural integrity of steel pipelines with wall metal losses and longitudinally-oriented grooves similar to cracks using different methodologies, for instance, the latest publications applying a finite element method [ 4 ] and a linear elastic fracture failure mode [ 5 ]. A rupture pressure prediction model for steel tubes affected by the stray current corrosion based on artificial neural network was applied in [ 6 ].…”
Section: Introductionmentioning
confidence: 99%